Marsupial Genome Sequences: Providing Insight into Evolution and Disease - Janine E. Deakin (Scientifica)
Marsupials (metatherians), with their position in vertebrate phylogeny and their unique biological features, have been studied for many years by a dedicated group of researchers, but it has only been since the sequencing of the first marsupial genome that their value has been more widely recognised. We now have genome sequences for three distantly related marsupial species (the grey short-tailed opossum, the tammar wallaby, and Tasmanian devil), with the promise of many more genomes to be sequenced in the near future, making this a particularly exciting time in marsupial genomics. The emergence of a transmissible cancer, which is obliterating the Tasmanian devil population, has increased the importance of obtaining and analysing marsupial genome sequence for understanding such diseases as well as for conservation efforts. In addition, these genome sequences have facilitated studies aimed at answering questions regarding gene and genome evolution and provided insight into the evolution of epigenetic mechanisms. Here I highlight the major advances in our understanding of evolution and disease, facilitated by marsupial genome projects, and speculate on the future contributions to be made by such sequences.